K problematice studia politiky a mezinárodních vztahů (Czech Journal of International Relations, 1966)
For Marxists, it is indisputable that politics is not just a skill, but a science. The question of its inclusion in the Marxist classification of social sciences has not yet been resolved, but in the ongoing debate about political science (respectively the science of politics, political science - termonology is not yet settled) a number of reasons have already been given for the research of problems falling within its field to be out of the study other social sciences separated. The urgency of systematic and continuous research of these problems flows, among other things. from the fact that politics plays an increasingly prominent role in social events today, and especially in events on an international scale, affecting the destinies of humanity to an unprecedented degree, and that more and more new questions are emerging that require theoretical and practical political solutions.